2018
DOI: 10.29259/sijdeb.v2i4.269-292
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cooperative's Characteristic on Financial Reporting Timeliness

Abstract: The purpose of this study is to do more in-depth analysis about factors that affect the financial reporting timeliness. The sample used in this study consists of 90 existing cooperatives in Denpasar city. Secondary data obtained from the Department of Cooperatives, Small, and Medium Enterprises. The primary data collected from the questionnaires. The analytical technique used is multiple linear regression. The results of this study found that profitability, leverage, and total assets are significantly effectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…This can be interpreted that the majority of the mining companies successfully attained profit and maintained to report their financial statements on time. This is in accordance with the study conducted by [20] and [21]. Their research said that profitability shows that the company has succeeded to obtain profits which send the good signal to the stakeholders and the shareholders.…”
Section: Resultssupporting
confidence: 89%
“…This can be interpreted that the majority of the mining companies successfully attained profit and maintained to report their financial statements on time. This is in accordance with the study conducted by [20] and [21]. Their research said that profitability shows that the company has succeeded to obtain profits which send the good signal to the stakeholders and the shareholders.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, with the increasing use of accounting information systems, the delivery of financial statements is said to be more timely. This conclusion is in accordance with Cleary (2017); Edmonds et al (2017); Susandya (2018) and it showed a positive and significant effect on the timeliness of financial statement submission. However, this result is slightly different from the conclusion of Borsellino et al (2020); Kythreotis and Constantinou (2016); Zaitul and Ilona (2019), which states that the information system does not affect the timeliness of financial reporting on large companies.…”
Section: Resultssupporting
confidence: 88%
“…This was in line with the report by Lubis (2016) on the cash receipt, cash expenditure, vendor, procurement, and staffing system to the timeliness of financial statement. The findings by Aula and Budisusetyo (2018); Susandya (2018) concluded that teamwork and internal control did not affect the accuracy of the financial statements submitted.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations